An Intelligent Customer-Driven Digital Solution to Improve Perioperative Health Outcomes Among Children Undergoing Circumcision and Their Parents: Development and Evaluation - Kwa, Zhi Yin; Li, Jinqiu; Loh, Dale Lincoln; Lee, Yang Yang; Liu, Guangyu; Zhu, Lixia; Pikkarainen, Minna; He, Honggu; Mali, Vidyadhar Padmakar (JMIR formative research, 2024)
Circumcision as a common elective pediatric surgery worldwide is a stressful and anxiety-inducing experience for parents and children. Although current perioperative interventions proved effective, such as reducing preoperative anxiety, there are limited holistic solutions using mobile apps. This paper aims to describe the development and primary evaluation of an intelligent customer-driven smartphone-based app program (ICory-Circumcision) to enhance health outcomes among children undergoing circumcision and their family caregivers. Based on the review of the literature and previous studies, Bandura's self-efficacy theory was adopted as the conceptual framework. A multidisciplinary team was built to identify the content and develop the apps. Semistructured interviews were conducted to evaluate the ICory-Circumcision. The ICory-Circumcision study was carried out from March 2019 to January 2020 and comprised 2 mobile apps, BuddyCare app and Triumf Health mobile game app. The former provides a day-by-day perioperative guide for parents whose children are undergoing circumcision, while the latter provides emotional support and distraction to children. In total, 6 participants were recruited to use the apps and interviewed to evaluate the program. In total, 4 main categories and 10 subcategories were generated from content analysis. ICory-Circumcision seemed to lean toward being useful. Revisions to ICory-Circumcision are necessary to enhance its contents and features before advancing to the randomized controlled trial. ClinicalTrials.gov NCT04174404; https://clinicaltrials.gov/ct2/show/NCT04174404.